2015
DOI: 10.1073/pnas.1415121112
|View full text |Cite
|
Sign up to set email alerts
|

Body size affects the evolution of eyespots in caterpillars

Abstract: Many caterpillars have conspicuous eye-like markings, called eyespots. Despite recent work demonstrating the efficacy of eyespots in deterring predator attack, a fundamental question remains: Given their protective benefits, why have eyespots not evolved in more caterpillars? Using a phylogenetically controlled analysis of hawkmoth caterpillars, we show that eyespots are associated with large body size. This relationship could arise because (i) large prey are innately conspicuous; (ii) large prey are more prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 49 publications
0
56
0
Order By: Relevance
“…Defences which putatively rely on intimidation, like eyespots, are ineffective on animals with smaller body sizes (Hossie et al, 2015). Furthermore, the switch between camouflage and aposematism can be size dependent (Valkonen et al, 2014).…”
Section: Sizementioning
confidence: 99%
“…Defences which putatively rely on intimidation, like eyespots, are ineffective on animals with smaller body sizes (Hossie et al, 2015). Furthermore, the switch between camouflage and aposematism can be size dependent (Valkonen et al, 2014).…”
Section: Sizementioning
confidence: 99%
“…Countershading (Edmunds & Dewhirst, 1994;Rowland et al, 2007), or reverse countershading (Rowland et al, 2008) can reduce bird predation, although not in all cases (Speed et al, 2005;Hossie & Sherratt, 2012). The defensive value of eyespots remains unclear, as it can be effective in itself (Hossie & Sherratt, 2013) or when interacting with countershading (Hossie & Sherratt, 2012), but it can also cause increased mortality (Hossie et al, 2015). Mimicking bird dropping can significantly reduce bird predation only when interacting with prey posture (Suzuki & Sakurai, 2015).…”
Section: Other Factors Influencing Predationmentioning
confidence: 99%
“…It has been demonstrated that defensive characters such as warning coloration are more effective when displayed in insects with large bodies (Forsman & Merilaita, 1999;Hossie, Skelhorn, Breinholt, Kawahara, & Sherratt, 2015). It has been demonstrated that defensive characters such as warning coloration are more effective when displayed in insects with large bodies (Forsman & Merilaita, 1999;Hossie, Skelhorn, Breinholt, Kawahara, & Sherratt, 2015).…”
Section: Character Evolution and Morphological Homoplasymentioning
confidence: 99%
“…The first hypothesis is that spines get lost or reduced because they confer no advantage below a certain size threshold. It has been demonstrated that defensive characters such as warning coloration are more effective when displayed in insects with large bodies (Forsman & Merilaita, 1999;Hossie, Skelhorn, Breinholt, Kawahara, & Sherratt, 2015). For example, defensive eyespots are effective in big caterpillars, but costly in small caterpillars, because they enhance detectability without providing a protective advantage in small caterpillars (Hossie et al, 2015).…”
Section: Character Evolution and Morphological Homoplasymentioning
confidence: 99%
See 1 more Smart Citation